Development of a New Minimalistic PHP Micro Framework: NOAPHP - Kabir Ahmed, Mohammed; Umar Gurama , Auwal; Dawaki, Mohammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Web application development projects demand efficient frameworks to address the challenges associated with complexity and accessibility. Noaphp, a lightweight PHP micro framework, was developed as a solution to simplify the development process, targeting small to intermediate web applications. This research outlines the key features and significance of Noaphp, including a secured database integration, a validation engine for server-side validation, and a simplified and secured authentication module. Emphasizing the importance of a structured and approachable framework, Noaphp adopts the Model-View-Controller (MVC) architecture. This methodology ensures a clean separation of concerns, enhancing modularity, maintainability, and scalability. Noaphp offers commitment to fostering collaboration and innovation within the developer community, positioning itself as a gateway for understanding framework fundamentals.